Depressive symptoms in the general population: The 7th Tromsø Study - Ole Kristian Grønli; Jørgen G. Bramness; Rolf Wynn; Anne Høye (Journal of Affective Disorders Reports, 2022)
Abstarct: Background: The prevalence of depressive symptoms may differ in various age groups. The aim of the study was to investigate the point-prevalence of depressive symptoms in the adult general population and in various age groups. The impact of sex, marital status, education, and social support on depressive symptoms was also explored. Methods: The population ≥40 years in the city of Tromsø, Norway, were invited to participate in the survey, of whom 64.7% (n=21,083) participated. All participants with a completed Hospital Anxiety and Depression Scale (HADS) were included in the study. A score ≥8 in the HADS depression subscale (HADS-D) was used to indicate caseness for depression. Results: The caseness for depression was 7.5% for men and 6.3% for women, overall 6.9%. The age groups 40-49 years and 80+ years had highest caseness. The overall HADS-D score for the total population was 2.8 (SD 2.7). The mean HADS-D for men (3.1; SD 2.8) was higher than for women (2.6; SD 2,6) (p<0.001). Low social support, low education and not living with a spouse was associated with higher risk for depressive symptoms. Limitations: The prevalence of depressive symptoms was based on a questionnaire, and represents only an estimate of depression in the population. Participants over 80 years were underrepresented, as fragile elderly and elderly living in nursing homes did not participate. Conclusions: Depressive symptoms were more prevalent in the youngest and oldest age groups. Participants reporting low social support, low education and not living with a spouse had higher risk for depressive symptoms.